Persecutory and Defamation as Barriers to Inheritance (Review of MaqÄá¹£id Shari'ah in a Compilation of Islamic Law) - Nabilah, Wardatun; Rizal, Deri; Warman, Arifki Budia (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
A Compilation of islamic law â€œKompilasi Hukum Islamâ€, which was ratified through Presidential Instruction (or now decree) No. 1 of 1991, is a modern codification of Islamic individual and family law that becomes the standard of judges' reference in resolving cases in religious courts. One of the critical parts of KHI is inheritance, which is the main focus of this paper. The article on inheritance in KHI is interesting for further review because it has a different legal provision to fiqh or qanun. Through the study of libraries with a philosophical approach, this paper intends to analyze the provisions that become a barrier to inheritance from the perspective of MaqÄá¹£id al-Sharia. This study shows that the obstacles to obtaining inheritance for reasons of persecution and slander, as mentioned in article 173 KHI, are some barriers to one obtaining inheritance that are not discussed as a barrier to inheritance in the classic fiqh book of severe persecution and slander. Through literature research, it is understood that the decree of persecution and slander is a barrier to inheritance in line with the MaqÄá¹£id al-Sharia, namely to protect the soul (hifz al-nafsi), then guard the property (hifz al-mÄl) and further maintain self-respect (hifz al-'Ird) Thus. However, severe persecution and slander are not listed in classical Islamic jurisprudence as a barrier to inheritance. With the study of MaqÄá¹£id al-Sharia, these two things are very appropriate to be applied in the rule of inheritance law, especially in Indonesia, so that these two acts cause very much harm to the victim (heir).Â â€œKompilasi Hukum Islamâ€, yang disahkan melalui Instruksi Presiden No. 1 Tahun 1991, merupakan kodifikasi modern hukum perseorangan dan keluarga Islam yang menjadi standar rujukan para hakim dalam menyelesaikan perkara di pengadilan agama. Salah satu bagian penting KHI adalah kewarisan, yang menjadi fokus utama dalam tulisan ini. Pasal tentang waris dalam KHI menarik dikaji lebih lanjut karena memiliki ketentuan hukum yang berbeda dengan fiqh atau qanun. Melalui studi pustaka dengan pendekatan filosofis, tulisan ini bermaksud menganalisis ketentuan yang menjadi penghalang warisan dari perspektif MaqÄá¹£idÂ al-SyarÄ«â€™ah. Hasil studi ini menunjukkan bahwa halangan mendapatkan warisan karena alasan penganiayaan dan fitnah, sebagaimana yang disebutkan dalam pasal 173 KHIÂ terdapat beberapa penghalang seseorang mendapatkan hak waris yang tidak dibahas sebagai penghalang kewarisan dalam kitab fiqh klasik yaitu penganiayaan berat dan fitnah.Â Melalui penelitian kepustakaan, dipahami bahwaÂ ketetapan penganiayaan dan memfitnah sebagai penghalang kewarisanÂ sejalan dengan MaqÄá¹£idÂ al-SyarÄ«â€™ah yakniÂ yakni untukÂ menjaga jiwa (hifáº“al-nafsi), kemudianÂ Â menjaga harta (hifáº“al-mÄl) danÂ selanjutnya menjaga kehormatan diri (hifáº“Â al-â€˜Irá¸) Maka, sekalipun penganiayaan berat dan fitnah tidak tercantum dalam fiqh klasik sebagai penghalang kewarisan, namun dengan kajian MaqÄá¹£idÂ SyarÄ«â€™ah, kedua hal ini sangat pantas diterapkan dalam aturan hukum waris, khususnya di Indonesia. Hal ini disebabkan karena dua perbuatan ini menyebabkanÂ sangat banyak mudaratÂ kepada korban (pewaris).